Food Security for All: Causes and Implications of Food Insecurity (Alternate Horizons, 2021)
Food is a basic right of all people, however, food security in Africa is being threatened. The main objective of this article is to uncover the causes and implications of food insecurity in Africa. The information was mainly obtained by reviewing literature with similar topics. Food security and food insecurity are both used to find out if people can or cannot access enough food.  Poverty, COVID-19, war and conflict, and climate change have major impacts on food security and this is explored in more detail in this article. Improved food security is very vital for a wider reduction of hunger and helps to overcome undernourishment, malnutrition, domestic violence, and poverty. The causes and implications of food insecurity in Africa need to be addressed to ensure that Africa is freed from hunger.
Keywords: Food security; Food insecurity; Africa; Causes; Implications